Influence of high-permittivity barriers on PD-parameters; Korus 2004; V. 2 - Lebedev S. M. Sergey Mikhailovich (2004, 2004)
It is a well-known fact that the breakdown voltage of dielectrics in the divergent field may be increased by using an additional insulating layer (a barrier) placed at the optimal position between the electrodes. In our previous works we reported that this effect is observed not only in the divergent electric field but also in moderately non-uniform and quasi-uniform electric fields. This paper is devoted to the investigation of the barrier effect in solid dielectrics in quasi-uniform electric field, in particular, the study of relationship between partial discharge activity and the barrier position in the insulating gap. It is established that PD-parameters depend on the barrier position in the gap. In particular, the ignition voltage of the partial discharge with magnitude of 10 pC is increased by 20...50% at the optimal barrier position compared to that for other barrier positions